Inception cohort study of workers exposed to toluene diisocyanate at a polyurethane foam factory: Initial one‐year follow‐up. Issue 11 (29th September 2014) - Gui, Wei; Wisnewski, Adam V.; Neamtiu, Iulia; Gurzau, Eugen; Sparer, Judith A.; Stowe, Meredith H.; Liu, Jian; Slade, Martin D.; Rusu, Olivia A.; Redlich, Carrie A.
<x xml:space="preserve">Abstract</x> Background Isocyanates are one of the most commonly reported causes of occupational asthma; however, the risks of developing isocyanate asthma in modern production facilities remain poorly defined. We evaluated TDI exposure and respiratory health among an inception cohort of workers during their first year of employment at a new polyurethane foam production factory. Methods Forty‐nine newly hired workers were evaluated pre‐employment, 6‐months, and 12‐months post‐employment through questionnaire, spirometry, and TDI‐specific serology. Airborne TDI levels were monitored by fixed‐point air sampling and limited personal sampling. Qualitative surface SWYPE™ tests were performed to evaluate potential sources of skin exposure. Results Airborne TDI levels overall were low; over 90% of fixed‐point air measurements were below the limit of detection (0.1 ppb). Over the first year of employment, 12 of the 49 original workers (24.5%) were lost to follow‐up, no additional workers were enrolled, and seven of the 49 original workers (14.2%) developed either new asthma symptoms (N = 3), TDI‐specific IgG (N = 1), new airflow obstruction (N = 1) and/or a decline in FEV1 ≥ 15% (N = 3), findings that could indicate TDI‐related health effects. The prevalence of current asthma symptoms was significantly higher in the workers lost to follow‐up compared to those who completed the 12‐month follow‐up (25% vs. 2.7%; P = 0.04). Conclusions The findings suggest possible early TDI‐related health effects in a modern polyurethane production plant. These findings also highlight the need for further longitudinal evaluation of these workers and the challenges of studying workers at risk for isocyanate asthma. Am. J. Ind. Med. 57:1207–1215, 2014. © 2014 Wiley Periodicals, Inc.